Need analysis of green chemistry-based practicum guidelines incorporating local wisdom on redox topic - Haritsma; Anti Kolonial Prodjosantoso (Indonesian Journal of Chemical Education, 2025)
Laboratory work in chemistry is crucial for students to develop their skills and enhance their understanding of chemical concepts. However, traditional laboratory methods often involve hazardous chemicals, posing risks to health and the environment. To address these concerns, integrating green chemistry principles and local wisdom into laboratory activities is necessary. This study explores the perspectives and needs of in-service chemistry teachers regarding practical work that incorporates green chemistry and local wisdom, specifically focusing on the redox topic. A qualitative approach was employed, using a semi-open-ended questionnaire to gather data from six in-service chemistry teachers. The questionnaire addressed six key aspects about practicum. The findings indicate that teachers recognize the importance of integrating green chemistry and local wisdom into practical activities, which enhances students' comprehension of chemistry concepts and promotes environmental sustainability and cultural appreciation. However, challenges such as limited resources, time constraints, and the need for appropriate materials remain. The study highlights the urgent need for developing laboratory instructions based on green chemistry and local wisdom, particularly for redox topics, to create a more relevant and effective chemistry education experience.